Knowledge, attitude and practices on nutrition and nutrition labeling of selected commercial foodservice establishments in Quezon City - Navarette, Marry Ann Recentes (2012)
This is a descriptive research with correlational analysis that assessed the knowledge, attitude and practices of 96 selected commercial foodservice establishments in Quezon City on nutrition labeling relative to the growing concern for providing healthy options in restaurants. Data were elicited from ninety-six (96) selected through stratified random sampling representing Casual Dining, Semi-fine/Fine Dining and Quick-service foodservices consisting of owners, managers, or R&D personnel. Results of this study showed low percentage (25%) of foodservice establishments practicing nutrition labeling. Those who did not [practice nutrition labeling indicated willingness to implement nutrition labeling (76%). Majority (78%) of the establishments agreed to mandatory nutrition labeling. Most of the foodservice establishments were familiar with various types of nutrition labeling, the most popular type of which were: the healthy choice logo followed by "good" and "bad" points, and sign post. Majority of the foodservice establishments surveyed had high scores on knowledge. Attitude towards the importance of nutrition and nutrition labeling was relatively high. With regards to healthful food preparation practices, semi-fine/fine dining scored the highest with most of the respondents stating that their establishment was known to offer nutritious choices like low-fat food and sugar-free food. Nonparametric correlation testing the interrelationship of knowledge, attitude and practice towards nutrition labeling showed that knowledge and practice have significant correlation among the three groups. Significant differences in the knowledge, attitude and practices toward nutrition labeling among the three categories of foodservice establishments using the Kruskal-Wallis Test, showed significant difference in the knowledge (p-value=0.012) among the three groups. Casual dining differed in knowledge level with that of semi-fine/fine dining (p-value=0.016) and quick-service (p-value=0.014), but semi-fine/fine dining and quick-service (p-value=0.577) did not have different knowledge levels. However, the foodservice establishments did not differ in their attitude (p-value=0.992) and practice (p-value=0.327) towards nutrition labeling. Implications of the study showed that there is likelihood for support from the industry once nutrition labeling was implemented. However, nutrition labeling policies must include regulations to guide and encourage the foodservice establishments. A more purposive and continuous campaign must be done to increase knowledge and practice of the industry practitioners.